Optical properties of near-surface exciton quantum wells - N. Atenco Analco (Superficies y vacío, 2001)
An overview of theoretical investigations on near-surface semiconductor quantum wells, whose optical properties areconsiderably affected by the interaction of the exciton with the sample surface is given. Near-surface quantum wells withboth weak and strong quantum confinement of excitons are considered. When the exciton quantum well is very close tothe sample surface, exciton dynamics is determined not only by characteristics of the quantum well, but also by theinteraction of the exciton with the sample surface. Optical spectra for various systems of near-surface quantum wells arediscussed. In addition, the optical manifestation of magnetoexcitons in near-surface quantum wells is also commented.